Pólipo esfenonasal como causa de mucocele esfenoidal: un diagnóstico a considerar - San Martín M., José T.; Arriagada G., Claudia; Bozán B., Héctor (Revista Hospital Clínico Universidad de Chile, 2013)
The sphenoidal sinus mucocele is a pseudocystic lesion of paranasal cavity (CPN). These injuries are probably underdiagnosed as they may be asymptomatic or cause nonspecific symptoms. The CT scan and the MRI increase the precision of the preoperative evaluation. We present a case of sphenoid sinus mucocele in a patient of 69 years old, who was admitted at our institution with 1 month evolution of persistent headache. Clinical presentation, diagnosis and treatment of this case are discussed as well as the review of the literature.